Addressing the Swedish Large Carnivore Controversy: Identifying Roadblocks in Collaborative Governance to Reduce Conflict - Bennett, Juliana; Sjölander-Lindqvist, Annelie; Sandström, Camilla; Larsson, Simon (Frontiers in Conservation Science, 2022)
In Europe, and many places throughout the world, the return, and preservation of large carnivores is escalating tensions between stakeholder groups, as well as between local actors and authorities. In Sweden, despite policies aimed at reducing conflict surrounding wildlife management, tensions seem to have intensified. This research investigates the collaborative governance model within Swedish wildlife management and what dampens the capacity to reduce ongoing tensions. In-depth interviews were conducted with stakeholders at different levels of wildlife management. Through an abductive approach combining empirical data from interviews and theories from the human-wildlife conflict and collaborative governance literature, we problematize the role of regional wildlife managers in this multilevel governance context, in exploration of ways to advance collaboration. Our model analyzes the challenges for wildlife managers to implement government policies based on broad international conventions while remaining accountable to local concerns. The results reveal that issues within the governance structure and relationships within management in terms of lack of legitimacy, trust, and participation, need to be addressed to create a viable collaborative governance regime capable of managing conflict.